Integrated metabolomic and transcriptomic analysis reveals the effects and mechanisms of Jingfang Baidu powder on acute lung injury - Zhu, Zimo; Cui, Baimei; Dai, Rong; Hu, Guoxian; Xu, Sue; Zhao, Xianfang; Wang, Wenjing; Li, Xiufang (Frontiers in Pharmacology, 2026)
BackgroundAcute lung injury (ALI) is one of the most prevalent respiratory diseases globally. Jingfang Baidu Powder (JF) is a clinically approved traditional Chinese medicine used for treating respiratory infectious diseases. However, its effects and mechanism in the context of ALI remain poorly understood. In this study, we investigated the potential of JF to alleviate ALI by reducing inflammation and necroptosis of lung epithelial cells.MethodsThe effects of JF on ALI were evaluated using an integrative pharmacological strategy. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was employed to identify the bioactive compounds of JF present in the serum of ALI mice, which are responsible for its therapeutic efficacy in treating ALI. ALI mouse models were established by the nasal drops of Poly (I∶C) over 3 days, followed by, intragastric administration of JF four times. We investigated Changes in lung function, inflammatory cytokines, pathological morphology of lung tissue, mitochondrial indicators, both transcriptomic and metabolomic profiles of the lung tissue, and necroptosis of lung epithelial cells.ResultsJF reduced airway resistance in ALI mice (p < 0.01) and respiratory frequency (p < 0.05); it lowered the levels of TNF-α in NLF, BALF, and serum (p < 0.05 or p < 0.01) and the content of IL-6 in NLF (p < 0.01), while improving the pathological damage of alveolar epithelial cells and mitochondria in ALI mice. Transcriptomics analysis revealed that JF potentially inhibits necroptosis, with seven constituents, notably hesperidin, identified as the putative active components of JF. Metabolomics analysis demonstrated that JF facilitated pulmonary epithelial cell repair through multifaceted modulation of metabolic pathways. Mechanistic validation indicates that JF can reduce the levels of NEC-related factors LDH and IL-18 in BALF (p < 0.05 or p < 0.01), as well as decrease the protein levels of p-MLKL and GSDME in lung tissue and the ratio of p-MLKL to MLKL (p < 0.05 or p < 0.01). Additionally, both JF and hesperidin can reduce NEC in A549 cells (p < 0.05 or p < 0.01).ConclusionJF can ameliorate ALI through various mechanisms, including its anti-inflammatory activity, inhibition of necroptosis, and enhancement of mitochondrial bioenergetics to promote ATP biosynthesis.